ANALYSIS OF THE EDUCATIONAL ETHICAL BEHAVIOUR - Bambulu, Wolter (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
The college is known as the last stage in education standard that prepare students to enter the professional world, but the facts show the practice of unethical behaviour is actually popular. No wonder so many human resources resulting moral defect. The fact is clearly indicates a step backward in education. As a place of learning and training in preparing qualified human resources, character, and ethics in their respective fields, then educations should start to fix this conditions. Research objectives are: (1) to know the existence of violations of ethics in educations occur in the environment, to Â describe students dealing with ethical violations in education, and to investigate the reasons behind students in International Business Administration (IBA) program commit to acts violations of ethics in education. Theories supporting research are academic integrity and academic misconduct and ethical behaviour. The informants are adjusted to the needs of the research that they are directly involved in educational activities in IBA program that is lecturers, students and staff.Â  Result and conclusion is there is violation of ethics in education at IBA program. Keywords: academic integrity and academic misconduct, ethical behaviour.